Strategi Komunikasi Pemasaran Bank BTN Kantor Cabang Cikarang dalam Mempromosikan Layanan BTN Prioritas - Utomo, Dendi Riyadi; Yuliantini, Yuliantini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the marketing communication strategy implemented by PT Bank Tabungan Negara (Persero) Tbk Cikarang Branch Office in promoting the BTN Prioritas service. Amidst intense competition in the banking industry within the High Net Worth Individuals (HNWI) segment, Bank BTN faces a strong perception challenge as a housing bank (mortgage) when penetrating the wealth management market. This study employs a qualitative method with a case study approach, where data collection is conducted through in-depth interviews, observation, and documentation studies. The findings indicate that Bank BTN Kantor Cabang Cikarang implements an Integrated Marketing Communication (IMC) strategy to strengthen the Customer Value Proposition